2013
DOI: 10.3892/ijmm.2013.1494
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of mTOR by lentivirus-mediated RNA interference suppresses atherosclerosis and stabilizes plaques via a decrease of macrophages by autophagy in apolipoprotein E-deficient mice

Abstract: Atherosclerotic plaque destabilization and rupture leads to acute coronary syndromes which cause serious damage to human health worldwide. However, there is currently a lack of efficient therapeutic methods. Mammalian target of rapamycin (mTOR) has been suggested to be involved in the development of atherosclerotic plaques and serves as a therapeutic target. The present study was performed to determine whether RNA interference (RNAi) of mTOR in vivo by LV‑mediated small hairpin RNA (shRNA) was capable of inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Previous studies reported that inhibition of mTOR by sirolimus or everolimus decreased the number of macrophages by inducing autophagy and suppressng atherosclerosis1011. Recent research also demonstrated that suppression of mTOR in an atherosclerotic mouse model by left ventricular-mediated RNAi inhibited atherosclerosis and stabilized plaques via a decrease of macrophages by autophagy28. Compared to macrophage activity, the elimination and injury of ECs is detrimental for atherosclerotic plaque stability.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported that inhibition of mTOR by sirolimus or everolimus decreased the number of macrophages by inducing autophagy and suppressng atherosclerosis1011. Recent research also demonstrated that suppression of mTOR in an atherosclerotic mouse model by left ventricular-mediated RNAi inhibited atherosclerosis and stabilized plaques via a decrease of macrophages by autophagy28. Compared to macrophage activity, the elimination and injury of ECs is detrimental for atherosclerotic plaque stability.…”
Section: Discussionmentioning
confidence: 98%
“…21 A recent study showed that knockdown of mTOR ameliorated dysregulated blood lipid metabolism and stabilized aortic atherosclerotic plaques by decreasing plaque area and increasing the size of fibrous cap and cap-to-core ratio via a decrease in the number of macrophages by autophagy in apolipoprotein E-deficient mice. 22 Another recent study showed that increased mTOR activity upregulated sterol regulatory element-binding protein-2-mediated cholesterol uptake through the phosphorylated retinoblastoma tumor suppressor protein. 23 In accordance with these studies, a recent clinical study also showed that mRNA expression of mTOR and other pro-inflammatory mediators, including tumor necrosis factor-α and monocyte chemotactic protein-1, was significantly higher in mononuclear cells extracted from carotid endarterectomy specimens compared with peripheral mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, induction of ALP in macrophages via knockdown of mTOR suppressed atherosclerosis and stabilized plaques (Wang et al . ). In TGF‐β‐induced calcification, atorvastatin decreased Ca deposition in VSMCs through induction of ALP (Liu et al .…”
Section: Introductionmentioning
confidence: 97%